Wirkung von Oxytocin auf das menschliche Schmerzerleben = Effect of oxytocin on human pain perception - Pfeifer, Ann-Christin; Ditzen, Beate; Neubauer, Eva; Schiltenwolf, Marcus (Der Schmerz, 2016)
BackgroundOver the years the effect of the neuropeptide oxytocin and its possible utilization for pain management has been increasingly more investigated and discussed. Initial results emphasized the effects of oxytocin with respect to labor and breastfeeding. Diverse animals studies were also able to demonstrate the effectiveness of the peptide in attachment behavior and pain perception; however, it is still unclear how oxytocin affects pain perception in humans. The potential therapeutic effectiveness of oxytocin could be particularly important for primary and secondary treatment of pain patients because chronification of pain can occur more frequently in this area.MethodsFor this review the databases PubMed, Medline und PsycINFO were searched using the terms oxytocin, pain, human and analgesic. The search resulted in a total of 89 original articles after excluding articles regarding labor pain, breastfeeding and animal studies. Only those studies were included which were carried out between 1994 and 2015. A total of 17 articles remained for inclusion in this review and included 13 studies on the exogenous application of oxytocin and 4 on measurement of oxytocin levels in plasma.ConclusionThis review article gives a summary of the current state of research on oxytocin and its direct and indirect association with human pain perception and emphasizes its relevance for the multimodal management of pain.